Airborne measurements of stratospheric constituents over Antarctica in the austral spring, 1987. II - Halogen and nitrogen trace gases - Coffey, M. T.; Mankin, William G.; Goldman, Aaron (1989)
The IR absorption spectra of the polar stratosphere, recorded by a Fourier transform spectrometer aboard the NASA DC-8 aircraft during the Airborne Antarctic Ozone Experiment, were used to derive vertical column amounts above flight altitude of HCl, HF, NO, NO2, ClONO2, and HNO3 in the region of disturbed ozone chemistry during September 1987. Significant reductions in the amounts of HCl, NO, NO2, and HNO3 were observed within the confines of the polar vortex, compared with amounts outside the vortex. When compared with the springtime observations by the same instrument in the Northern Hemisphere, the HCl and NO2 species displayed the most dramatic depletions. The results obtained are generally in agreement with the earlier ground measurements conducted at the McMurdo Station.